2017
DOI: 10.1245/s10434-017-6300-x
|View full text |Cite
|
Sign up to set email alerts
|

Oncological Assessment of Stent Placement for Obstructive Colorectal Cancer from Circulating Cell-Free DNA and Circulating Tumor DNA Dynamics

Abstract: Despite equivalent clinical success rates, SEMS placement increased plasma levels of cfDNA and ctDNA by tumor manipulation, but TDT did not. Colonic stenting showed oncological risk in terms of molecular analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
52
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 26 publications
0
52
0
1
Order By: Relevance
“…In addition, stent insertion for obstructive CRC may result in an increase in CK20 mRNA [21], cell-free DNA, circulating tumor DNA [24], and viable circulating tumor cells (v-CTCs) [25]. To accurately evaluate the effect of tumor manipulation by the radial force generated when a SEMS expands, the influence of additional surgery, such as colostomy, should be avoided as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, stent insertion for obstructive CRC may result in an increase in CK20 mRNA [21], cell-free DNA, circulating tumor DNA [24], and viable circulating tumor cells (v-CTCs) [25]. To accurately evaluate the effect of tumor manipulation by the radial force generated when a SEMS expands, the influence of additional surgery, such as colostomy, should be avoided as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…A multicentre retrospective study also indicated that the long-term oncologic outcome of the SEMS group was similar or slightly better than that of the ES group among all patients with stage II or III colon cancer [23]. Moreover, a recent study reported that SEMS placement increased plasma levels of cell-free DNA and circulating tumour DNA by tumour manipulation [24], although several clinical studies reported no signi cant differences in the long-term survival rates regardless of stent placement before surgery [25,26]. Moreover, Li et al and Gianotti et al reported improved survival of the SEMS group throughout the follow-up period [27,28].…”
Section: Discussionmentioning
confidence: 95%
“…Since the rst reported use of SEMS in 1991, SEMS as a bridge of surgery has been widely developed because of its good short-term results, but its longterm oncology results are worrying (31). Several studies (32)(33)(34)(35) have found that SEMS implantation can cause tumor cells to release into the circulatory system, but Ishibashi (32) believes that these tumor cells are not cancer stem-like cells, which can be quickly removed by the body, so they will not cause distant metastasis of the tumor.…”
Section: Discussionmentioning
confidence: 99%